2024
DOI: 10.3390/antiox13030270
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics of Natural Antioxidants in Broilers

Ioanna Kouvedaki,
Athanasios C. Pappas,
Peter F. Surai
et al.

Abstract: The broiler industry supplies high-quality animal protein to the world. The ban of antibiotics as growth promoters has opened the way for plenty of phytochemicals and antioxidants to be explored. This study summarizes the use of natural antioxidants in a broiler diet as a way through which to deal with stressors, as well as their effects on the expression of various genes. The transcriptional factors and genes involved in the regulation of redox homeostasis are described and emphasis is placed on nuclear facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…In recent years, hesperidin has attracted extensive attention in livestock and poultry breeding because of its antioxidant, lipid metabolism regulation, anti-inflammatory and other biological activities ( Hager-Theodorides et al., 2021 ). It has been reported that hesperidin can effectively relieve the symptoms of heat stress in broilers and improve the growth efficiency of the animals, so it is gradually recommended to be used in animal feed as a feed additive ( Kamboh et al., 2013 ; Kouvedaki et al., 2024 ). Studies have found that hesperidin regulates gut flora to alleviate liver damage in mice ( Li et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hesperidin has attracted extensive attention in livestock and poultry breeding because of its antioxidant, lipid metabolism regulation, anti-inflammatory and other biological activities ( Hager-Theodorides et al., 2021 ). It has been reported that hesperidin can effectively relieve the symptoms of heat stress in broilers and improve the growth efficiency of the animals, so it is gradually recommended to be used in animal feed as a feed additive ( Kamboh et al., 2013 ; Kouvedaki et al., 2024 ). Studies have found that hesperidin regulates gut flora to alleviate liver damage in mice ( Li et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%